Skrining Penyakit Menular Pada Ibu Hamil Di Rumah Sakit Umum Daerah Kwaingga Kabupaten Keerom - Rini Prastyawati; Tika Romadhonni; Thiara Pradasari (Poltekkes Kemenkes Mataram, 2021)
A research entitled Infectious Disease Screening for Pregnant Women at the Kwaingga, Keerom Regency. The purpose of this study was to determine the results of Hepatitis B and Syphilis screening in pregnant women at Kwaingga Keerom Regional Hospital. The population in this study were all patients who came for antenatal care at the Kwaingga Keerom District Hospital. The sample in this study was the blood of pregnant women used as serum with a total sample of 30 samples. The examination method is the immunochromatography method. This screening was carried out for 1 month, from January 20 to February 25, 2020. HBsAg and TP Rapid examination results obtained for HBsAg as many as 7% positive infected with Hepatitis B and 93% other negative results, and the results of TP Rapid examination were obtained results as much as 3% positive for syphilis and 97% were negative. so, from the results of HBsAg and TP Rapid examination, positive samples of hepatitis B and syphilis were still obtained in pregnant women at Kwaingga Keerom Regional Hospital.